Use of a high b‐value for diffusion weighted imaging of peritumoral regions to differentiate high‐grade gliomas and solitary metastases. Issue 1 (15th September 2014) - Han, Chengkun; Huang, Shumin; Guo, Jianfeng; Zhuang, Xiongjie; Han, Haiwei
<x xml:space="preserve">Abstract</x> Background To determine whether apparent diffusion coefficient (ADC) values obtained using a b‐value of 3000 s/mm2 can be used to differentiate high‐grade glioma (HGG) from solitary metastases (SM). Methods Forty patients underwent conventional magnetic resonance imaging (MRI) and standard and high b‐value diffusion‐weighted imaging (DWI). Minimum, maximum, and mean ADC values (ADCMIN, ADCMAX, and ADCMEAN, respectively) were measured from ADC maps obtained for the two b‐values for each subject. ADC ratios were also measured. A receiver operating characteristic (ROC) curve analysis was used to determine the cutoff ADC value for distinguishing between HGG and SM. Results All ADC values for the peritumoral region of the HGGs examined were lower than those for the SM. Furthermore, a larger statistical difference was observed for ADCMIN, ADCMAX, and ADCMEAN values at a b‐value of 3000 s/mm2 versus 1000 s/mm2 (P < 0.0001, P = 0.0010, and P = 0.0001 versus P = 0.0001, 0.0030, and 0.0002, respectively). A discriminant analysis identified the greatest log likelihood for the ADCMIN values obtained at a b‐value of 3000 s/mm2, and the cutoff value for differentiating HGG and SM was 0.890 × 10−3 mm/s2. Conclusion ADC values from DWI using a high b‐value were found to distinguish HGG and SM. The lowest degree of overlap was obtained when an ADCMIN value was obtained at a b‐value of 3000 s/mm2. J. Magn. Reson. Imaging 2015;42:80–86. © 2014 Wiley Periodicals, Inc.